Challenges in the pharmacological management of epilepsy and its causes in the elderly. (April 2016) - Ferlazzo, Edoardo; Sueri, Chiara; Gasparini, Sara; Aguglia, Umberto
Graphical abstract: Abstract: Epilepsy represents the third most common neurological disorders in the elderly after cerebrovascular disorders and dementias. The incidence of new-onset epilepsy peaks in this age group. The most peculiar aetiologies of late-onset epilepsy are stroke, dementia, and brain tumours. However, aetiology remains unknown in about half of the patients. Diagnosis of epilepsy may be challenging due to the frequent absence of ocular witnesses and the high prevalence of seizure-mimics (i.e. transient ischemic attacks, syncope, transient global amnesia or vertigo) in the elderly. The diagnostic difficulties are even greater when patients have cognitive impairment or cardiac diseases. The management of late-onset epilepsy deserves special considerations. The elderly can reach seizure control with low antiepileptic drugs (AEDs) doses, and seizure-freedom is possible in the vast majority of patients. Pharmacological management should take into account pharmacokinetics and pharmacodynamics of AEDs and the frequent occurrence of comorbidities and polytherapy in this age group. Evidences from double-blind and open-label studies indicate lamotrigine, levetiracetam and controlled-release carbamazepine as first line treatment in late-onset epilepsy.